AMISOM: charting a new course for African Union peace missions. Issue 2 (3rd April 2017) - Wondemagegnehu, Dawit Yohannes; Kebede, Daniel Gebreegziabher
ABSTRACT: The African Union Mission in Somalia (AMISOM) is an atypical peace support operation (PSO) that has evolved sui generis and continues to chart its own trajectory politically and militarily. With a view to contributing to the African Union (AU) Commission's policymaking process and articulation of its PSO doctrine, this article examines AMISOM's various distinct features, especially as they relate to the mandating process, mission support arrangements, and interactions with the Somali National Security Forces (SNSF). The article argues that there is a clear need for the AU to articulate a PSO doctrine appropriate to the types of missions which the AU undertakes, both now and in the near future. AMISOM's initial mandating process was event-driven rather than context-driven, and the mission operated was based on a logistic supply arrangement that was at times not in sync with its overall operational demands. While the mission has multifaceted interactions with the SNSF, the interplay was fragmented, not least due to a multiplicity of actors and interests. A reading of the AMISOM experience underlines that the design of the AU's contemporary peace missions' doctrine should be centred on an integrated and mutually-reinforcing relationship among operations, institution-building, logistical support, and politics.